Higher education, initial vocational education and training and continuing education and training: where should the balance lie? - Mason, Geoff [Verfasser] (My University, 2020)
"This paper reviews evidence on two serious imbalances in the UK education and training system: 1. The heavy bias in public spending on initial education and training (for 18-24-year olds) towards higher education at the expense of further education and vocational education and training. 2. The very weak government support for continuing education and training (for adults aged 25-plus) compared to that provided for initial education and training for new entrants to the workforce. The effects of these imbalances are compounded by a marked reluctance by many employers to invest in work-based training, especially long-duration apprenticeship training. In a concluding policy section, the paper discusses ways in which both major imbalances could be reduced by abolishing tuition fees: first, for all Further Education courses up to Level 5 (for example, Foundation degrees, Higher National Diplomas); and second, for work-related, community learning and general-interest courses which do not necessarily lead to formal qualifications. It also considers options for short-duration continuing education and training for adults of all ages to be encouraged without undermining current efforts to reform and improve apprenticeship training. (author's abstract; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 1.3 Berufliche Erstausbildung; I 2.2.1 Westeuropa; Bildungssystem; Bildungsfinanzierung; Hochschulbildung; Berufsausbildung; Höhere Berufsbildung; Weiterbildung; Vereinigtes Königreich